KREMNIY ASOSIDAGI FOTOELEMENTLARDA TEKSTURALAR OLISH TEXNOLOGIYASI - Ismaylov, Q.A.; Ismaylov, B.Q.; Kamalov, X.U.; Zikrillaev, X.F.; Sattorov, A.A.; Norqulov, N. (SCIENCE and SOCIETY, 2024)
A texture was created on the surface of a silicon single crystal wafer. It has been discovered that the efficiency of photovoltaic cells can be improved by controlling the texture formation process. A technology was created to obtain an accurate height texture by controlling time. It was found that the short circuit current and open circuit voltage of the photocell increase when the height of the created textures is in the range of 3-15 microns.